PENGARUH BYSTANDER EFFECT DAN WHISTLEBLOWING SYSTEM TERHADAP PENCEGAHAN FRAUD PENGELOLAAN KEUANGAN DESA DENGAN PEMODERASI MORALITAS DAN SISTEM KEUANGAN DESA - Wuryandini, Ayu Rakhma; Panigoro, Nurharyati (Universitas Sarjanawiyata Tamansiswa, 2024)
The purpose of this study was to analyze the influence of factors that influence fraud prevention in village financial management with the morality of village officials and Siskeudes as moderating variables. This type of descriptive quantitative research with the Multiple Regression Analysis (MRA) approach, the research population is nine villages spread across Kabila Bone District. Researchers will use a survey and distribute 54 questionnaires according to Permendagri number 20 of 2018, namely village apparatus as a research sample with purposive sampling as a sampling technique. The results of this study are partial bystander effect tests; whistleblowing system has no significant effect on preventing financial management fraud, Simultaneous bystander effect test and whistleblowing system have no significant effect on preventing financial management fraud, interaction between bystander effect and village apparatus morality on financial management fraud prevention is significant and able to moderate, interaction bystander effect and siskeudes on the prevention of financial management fraud is significant and able to moderate, the interaction between the whistleblowing system and the morality of village officials on the prevention of financial management fraud is insignificant and unable to moderate, the interaction between the whistleblowing system and siskeudes on the prevention of financial management fraud is significant and able to moderate.